Foreign policy and cooperation: from speech to action - Guzmán León, Alicia (2016)
This article presents the scenario of foreign and international cooperation policies in Ecuador prior to Rafael Correa ascend to power. In this case, cooperation in the frame of Plan Colombia and the Andean Regional Initiative were considered examples of this policy. The author illustrates the new policies of the current government has been produced by a paradigm guiding Ecuadorian internal and external policies and its link with the association to ALBA, to finish with a confrontation between retorics and practice in commercial and co-operation issues within different countries in South America.